The rise and fall of English inflectional morphology - Juola, P; Plunkett, K (1998)
Children acquire noun inflections before they acquire verb inflections. Noun inflections are also less affected by language disorders than verb inflections. We describe a single-system connectionist model of English noun and verb inflection which captures these facts of acquisition and atrophy, as well as other well-established developmental characteristics such as U-shaped learning and the ability to generalise to novel forms. The model makes the novel experimental prediction that irregular nouns are less affected by damage than irregular verbs, even though irregular nouns are harder to learn.